A New Root Rot Disease Complex in Teak - Bakshi, B. K.; Singh, Sujan; Singh, Ujagar (Indian Forester, 1966)
The outbreak of a root-rot disease in teak in Demonstration Area, New Forest which has already been noticed (Bakshi, 1966) is now described in detail. The pathogens concerned are Polyporus zonalis Berk and Peniophora rhizoomorpho-sulphurea sp. Nov. The decay in the roots causes wind throw of affected trees. P. rhizomorpho-sulphurea is described from sporophore and in culture. P. zonalis which causes butt and root-rot infects trees through injury. P. rhizomorpho-sulphurea possesses an ability of intense saprophytic colonization of stumps and spreads to adjoining trees mainly through rhizomorphs. Control of the diseases in the existing stand may be obtained by stump treatment, trenching and maintaining hygienic conditions.